2021
DOI: 10.1044/2021_jslhr-20-00660
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic Facilitation of Oral Vocabulary Acquisition in Children With Hearing Loss

Abstract: Purpose Learning spoken words can be challenging for children with hearing loss who communicate orally and who are known to have weaker oral vocabulary skills than age-matched children who hear. Since vocabulary skills play a crucial role in reading and literacy acquisition, and academic success, it is important to identify effective vocabulary acquisition strategies for children with hearing loss. The aim of this study was to examine whether the incidental presence of orthography can facilitate or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This differential pattern of orthographic facilitation in the two tasks (i.e., picture-naming and PWM) raises questions about the mechanism underlying this effect in different groups (Colenbrander et al, 2019; Salins et al, 2021). Picture naming involves retrieving the phonology of a word from its meaning (represented by the picture in this study), whereas PWM requires participants to retrieve meaning from the phonology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This differential pattern of orthographic facilitation in the two tasks (i.e., picture-naming and PWM) raises questions about the mechanism underlying this effect in different groups (Colenbrander et al, 2019; Salins et al, 2021). Picture naming involves retrieving the phonology of a word from its meaning (represented by the picture in this study), whereas PWM requires participants to retrieve meaning from the phonology.…”
Section: Discussionmentioning
confidence: 99%
“…Although accuracy on this task was at ceiling and no facilitation effect was observed, participants were faster to respond correctly to words learned with spellings. This paradigm has since been used to demonstrate the orthographic facilitation of oral vocabulary learning in different groups of children with typical and atypical development (Baron et al, 2018; Lucas & Norbury, 2014; Mengoni et al, 2013; Ricketts et al, 2015; Salins et al, 2021).…”
mentioning
confidence: 99%
“…The methodological quality of the 25 studies from 26 papers was analyzed, because two papers reported the results of the same study (Wicha, Chakpitak, & Adipattaranan, 2012;Wicha, Sharp, et al, 2012). Eight group studies included typical hearing groups as controls, making randomization not feasible (Blaiser et al, 2015;Houston et al, 2005;Majorano et al, 2017;Robertson et al, 2017;Salins et al, 2021;Stiles et al, 2013;van Berkel-van Hoof et al, 2020;Walker & McGregor, 2013). The RoB results can be seen in Figure 2.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…There were 13 studies that took place in the United States of America. The others were conducted in Australia (Paatsch et al, 2006;Salins et al, 2021), Hong Kong (Fung et al, 2005), India (Joy et al, 2019), Iran (Zamani et al, 2016), Italy (Majorano et al, 2017), the Netherlands (van Berkel-van Hoof et al, 2020;Wauters et al, 2001), South Africa (van Staden, 2013, Thailand (Plaewfueang & Suksakulchai, 2020;Wicha, Chakpitak, & Adipattaranan, 2012), and Turkey (Birinci & Sarıçoban, 2021).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Word learning was assessed using behavioral and eye-tracking data from picture naming and picture-word matching tasks. Results showed an orthographic boost to oral vocabulary learning in children with hearing loss, and this benefit was maintained throughout the week [7]. Therefore, it is important to study the corpus-based English pronunciation learning system [8].…”
Section: Introductionmentioning
confidence: 99%